Electromagnetic wave absorbing film and method for preparing the same

A two-dimensional sheet-like multilayer structure with soft magnetic composite materials and amorphous carbon layers addresses the limitations of single-layer absorbers by enhancing impedance matching and absorption bandwidth, improving microwave absorption and mechanical stability.

JP2025013302AActive Publication Date: 2025-01-24SUZHOU BOTAO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024112584
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-13
Filing Date
2024-07-12
Publication Date
2025-01-24
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

Conventional electromagnetic wave absorbers are limited by single-layer structures that fail to provide effective absorption across diverse frequency bands, necessitating the development of multilayer materials with improved impedance matching and absorption characteristics.

Method used

A two-dimensional sheet-like multilayer structure composed of soft magnetic composite materials and amorphous carbon layers, integrated with a lattice arrangement, enhances impedance matching and absorption bandwidth, using a combination of soft magnetic alloys like Fe9.6-Si5.4-Al and Al2O3, and a polymer elastomer matrix.

Benefits of technology

The multilayer structure significantly improves microwave absorption characteristics by balancing functional materials, increasing effective absorption bandwidth and mechanical stability, while preventing surface carbon formation and enhancing corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013302000001_ABST
    Figure 2025013302000001_ABST
Patent Text Reader

Abstract

To provide an electromagnetic wave absorbing film and a method for preparing the same which improve the matching between the impedance of an electromagnetic wave absorbing film and the impedance of free space by regularly arranged structure design effectively, thereby increasing the effective absorption bandwidth.SOLUTION: An electromagnetic wave absorbing film includes a substrate 1 and an electromagnetic wave absorbing layer 2 provided on the substrate and including a matrix 21 and electromagnetic wave absorbing units 22. The plurality of electromagnetic wave absorbing units are arranged in a lattice pattern within the matrix, and the electromagnetic wave absorbing layer is made of a soft magnetic composite material and a polymer elastomer, the mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer is in the range of 10 to 80%, and the plurality of absorbing units arranged in a lattice pattern within the matrix are used.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of electromagnetic wave absorbing materials, in particular to an electromagnetic wave absorbing film and a method for preparing the same. [Background technology]

[0002] Electromagnetic shielding and electromagnetic absorbing materials are commonly used to eliminate electromagnetic interference and protect against electromagnetic radiation. Compared with electromagnetic shielding technology, using electromagnetic absorbing materials is the most effective way to eliminate electromagnetic interference. Electromagnetic absorbing materials can absorb most of the electromagnetic waves irradiated on their surface, convert them into heat energy or other forms of energy, and dissipate them, and have already been widely used in cutting-edge technologies such as aviation, medical radiation safety, microwave processing technology, and self-driving cars.

[0003] The absorption characteristics of electromagnetic wave absorbing materials depend on their impedance matching and attenuation characteristics. When the impedance matching is good and the attenuation characteristics are strong, the reflection of electromagnetic waves is low, the dissipation power of electromagnetic waves incident on the electromagnetic wave absorbing material is high, and the absorption characteristics are good. Electromagnetic wave absorbing materials usually include resistive types (e.g., SiC and graphite), dielectric types (e.g., BaTiO3, BiFeO3), magnetic and dielectric types (e.g., ferrite, FeSiAl), etc. Compared with other electromagnetic wave absorbing materials, soft magnetic materials have the advantages of high magnetic permeability and magnetic loss, good impedance matching characteristics, and strong absorption characteristics, making them the most practical electromagnetic wave absorbing materials and widely used in the communication field. Therefore, there is a great potential for the development of high-performance soft magnetic materials to be used in electromagnetic wave absorbing materials.

[0004] In addition, in the prior art, most electromagnetic wave absorbing materials are composed of a single-layer absorbing sheet, which is formed by combining an electromagnetic wave absorbing material with a matrix to provide a certain thickness and achieve electromagnetic wave absorbing properties in a specific frequency band. With the diversification of electromagnetic wave absorption scenarios, there is great potential in developing electromagnetic wave absorbing materials with multi-layer broadband radio wave absorbing properties.

[0005] Therefore, the object of the present invention is to provide an electromagnetic wave absorbing film and a preparation method thereof to solve the above technical problems. Summary of the Invention [Problem to be solved by the invention]

[0006] In order to overcome the above-mentioned shortcomings, the object of the present invention is to provide an electromagnetic wave absorbing film and a preparation method thereof, which has a reasonable structural design and a simple preparation method, the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern in a matrix, and the regularly arranged structural design can effectively improve the matching between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increase the effective absorption bandwidth, and the soft magnetic alloy composite material uses a two-dimensional sheet-like multi-layer structure including a soft magnetic alloy, an Al2O3 layer, and an amorphous carbon layer from the inside to the outside, and compared with a single-layer soft magnetic alloy, the multi-layer structure has good properties that can be compatible with various functional materials, and can be expected to be used in a wide range of applications, and a preparation method thereof. [Means for solving the problem]

[0007] The object of the present invention is achieved by the following technical means.

[0008] An electromagnetic wave absorbing film comprising a substrate and an electromagnetic wave absorbing layer provided on the substrate, the electromagnetic wave absorbing layer comprising a matrix and electromagnetic wave absorbing units, a plurality of the electromagnetic wave absorbing units being arranged in a lattice pattern within the matrix, the electromagnetic wave absorbing layer being made of a soft magnetic composite material and a polymer elastomer, and the mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer being in the range of 10 to 80%.

[0009] The electromagnetic wave absorbing film of the present invention has a rational structural design, and the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern within a matrix. The regularly arranged structural design can effectively improve the match between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increase the effective absorption bandwidth.

[0010] The soft magnetic composite material has high saturation magnetic induction strength and low coercive force, and can effectively isolate electromagnetic interference and magnetic field interference. The polymer elastomer acts as a filler and binder in the electromagnetic wave absorbing layer, and the soft magnetic composite material is uniformly dispersed in the electromagnetic wave absorbing layer, thereby improving the electromagnetic wave absorption effect. The soft magnetic composite material and the polymer elastomer are tightly bonded to increase the mechanical strength and stability of the electromagnetic wave absorbing layer.

[0011] Moreover, in the above-mentioned electromagnetic-wave-absorbing film, the soft magnetic composite material is a powder, the powder has a thickness of 0.5 to 1.5 μm and a particle size D50 of 30 to 100 μm.

[0012] In the above-mentioned electromagnetic-wave-absorbing film, the soft magnetic composite material has a two-dimensional sheet-like multilayer structure including, from the inside to the outside, a soft magnetic alloy, an Al2O3 layer, and an amorphous carbon layer.

[0013] Soft magnetic alloys have the advantages of low magnetocrystalline anisotropy constant and high permeability, but at the same time, they have the disadvantages of high dielectric constant and poor impedance matching. Therefore, in order to obtain better electromagnetic wave absorption properties, the present invention optimizes the soft magnetic alloy, and uses a two-dimensional sheet-like multi-layer structure including soft magnetic alloy, Al2O3 layer, and amorphous carbon layer from inside to outside in the soft magnetic alloy composite material. Compared with a single-layer soft magnetic alloy, the multi-layer structure has good properties that can be compatible with various functional materials, and can adjust the dielectric constant, permeability, and rich interface structure to achieve impedance matching and increase loss. By providing an Al2O3 layer between the soft magnetic alloy and the amorphous carbon layer, it not only prevents the generation of carbon nanomaterials on the surface of the soft magnetic composite material, but also introduces multiple scattering and reflection mechanisms to improve the microwave absorption properties, and at the same time, this multi-layer structure can also play a shielding protection role and improve the corrosion resistance of the soft magnetic composite material.

[0014] In the above-mentioned electromagnetic-wave-absorbing film, the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.

[0015] Preferably, the soft magnetic alloy is an iron-silicon-aluminium soft magnetic alloy, also known as Sendust alloy, with the main components being Fe9.6-Si5.4-Al.

[0016] In the above electromagnetic wave absorbing film, the substrate is at least one of a PET film, a PI film, a PP film, a PEI film, a polyether ether ketone, a phenolic resin, a PE film, a PC film, a PS film, and a PVC film, the thickness of the substrate is 10 to 300 μm, and the thickness of the electromagnetic wave absorbing layer is 0.1 to 2 mm.

[0017] In the electromagnetic-wave-absorbing film, the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.

[0018] The present invention also relates to a method for preparing the electromagnetic-wave-absorbing film described above, comprising the following steps S1 to S5: S1: A step of uniformly mixing a soft magnetic composite material and a polymer elastomer to obtain a first mixture; S2: Add the first mixture into a stirrer, then add a solvent, mix the first mixture and the solvent in a mass ratio of 1-5:1-5, and stir thoroughly until homogenous to obtain a second mixture; S3: A process in which the second mixture is applied onto a substrate, spread evenly over the substrate with a scraper, and then placed for 1 to 10 minutes on an acrylic plate having multiple cylindrical permanent magnets arranged in a lattice with their north poles facing upwards, followed by heating, solidification, and molding to obtain an electromagnetic wave absorbing film.

[0019] The soft magnetic composite material has high magnetic induction strength due to multiple cylindrical permanent magnets with their north poles facing upwards in a lattice arrangement arranged on an acrylic plate. Under the action of the magnetic field of the cylindrical permanent magnets, they approach in the approaching direction and come together based on the lattice arrangement of the cylindrical permanent magnets to form multiple electromagnetic wave absorbing units. Based on the upward magnetic direction of the north poles of the cylindrical permanent magnets, the soft magnetic composite material of the multiple electromagnetic wave absorbing units is not interfered with by adjacent magnets, and a stable shape can be obtained.

[0020] In addition, in the above-mentioned preparation method of the electromagnetic-wave-absorbing film, the electromagnetic-wave-absorbing powder is a soft magnetic composite material, and the preparation method includes the following steps S1 to S2: S1: Mixing an ammonium formate solution, a soft magnetic alloy powder, and aluminum sulfate, and ultrasonically dispersing the mixture for 10 to 3 minutes to obtain a mixed solution, heating the mixed solution in a water bath at 75 to 85°C, maintaining the mixture at that temperature and reacting it with stirring for 1 to 2 hours, washing the mixture with ethanol multiple times and magnetically separating the mixture, drying the mixture in an oven at 40 to 50°C for 1 to 3 days, and then annealing the mixture at 350 to 450°C for 2 hours to obtain a soft magnetic alloy powder coated with an Al2O3 layer; S2: The soft magnetic alloy powder coated with the Al2O3 layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400°C at 3-6°C / min under an argon protective atmosphere with a gas flow rate of 50-100mL / min, and then acetylene gas is introduced at a flow rate of 20-30mL / min to react for 0.5-1 hour. After the reaction is completed, the acetylene gas is stopped, the material is slowly cooled to 25°C, and taken out to obtain a soft magnetic composite material.

[0021] First, an Al2O3 layer is coated on the surface of the soft magnetic alloy powder by the sol-gel method, and then an amorphous carbon layer is introduced on the surface of the soft magnetic alloy by the CCDV method. The highly resistive amorphous carbon layer can reduce the dielectric constant of the magnetic metal, achieve good impedance matching between the absorbing material and free space, and improve the microwave absorption properties. Effect of the Invention

[0022] Compared with the prior art, the present invention has the following advantageous effects: (1) The electromagnetic wave absorbing film disclosed by the present invention has a reasonable structural design, and the electromagnetic wave absorbing layer uses a plurality of absorbing units arranged in a lattice pattern in the matrix, and the regularly arranged structural design can effectively improve the matching between the impedance of the electromagnetic wave absorbing film and the free space impedance, and increase the effective absorption bandwidth. The electromagnetic wave absorbing layer is made of a soft magnetic composite material and a polymer elastomer, and the soft magnetic composite material has high saturation magnetic induction strength and low coercive force, and can effectively isolate electromagnetic interference and magnetic field interference. The soft magnetic composite material and the polymer elastomer are tightly bonded to increase the mechanical strength and stability of the electromagnetic wave absorbing layer. (2) The electromagnetic wave absorbing film disclosed by the present invention uses a two-dimensional sheet-like multi-layer structure including a soft magnetic alloy, an Al2O3 layer, and an amorphous carbon layer from the inside to the outside of the soft magnetic alloy composite material, and compared with a single-layer soft magnetic alloy, the multi-layer structure has good properties that can be used with various functional materials, and has the effect of adjusting the dielectric constant, permeability, and rich interface structure to achieve impedance matching and increase loss. By providing an Al2O3 layer between the soft magnetic alloy and the amorphous carbon layer, not only can the generation of carbon nanomaterials on the surface of the soft magnetic composite material be prevented, but also multiple scattering and reflection mechanisms are introduced to improve the microwave absorption properties, and at the same time, this multi-layer structure can act as a shielding protection and improve the corrosion resistance of the soft magnetic composite material. (3) The preparation method of the electromagnetic wave absorbing film disclosed by the present invention has a reasonable preparation process, is simple and controllable, and is highly flexible. A plurality of cylindrical permanent magnets with their north poles facing upwards are arranged in a lattice on an acrylic plate to form a plurality of electromagnetic wave absorbing units based on the lattice arrangement of cylindrical permanent magnets. Due to the upward magnetic direction of the north poles of the cylindrical permanent magnets, the soft magnetic composite materials of the plurality of electromagnetic wave absorbing units are not interfered with by adjacent magnets, and a stable shape can be obtained. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic cross-sectional view of an electromagnetic-wave-absorbing film according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, the technical means in the embodiments of the present invention will be described clearly and in detail with reference to Comparative Example 1, Example 1, Comparative Example 2, Example 2, specific test data, and Figure 1, but it goes without saying that the described embodiments are only some of the embodiments of the present invention and do not include all of the embodiments. All other embodiments obtained by those skilled in the art on the basis of the embodiments of the present invention without any creative activity are all within the scope of protection of the present invention.

[0025] The raw materials used in Comparative Example 1, Example 1, Comparative Example 2, and Example 2 are all commercially available raw materials commonly used in industry.

[0026] In Comparative Example 1 and Example 1, electromagnetic wave absorbing materials were provided.

[0027] Comparative Example 1 Comparative Example 1 is a sendust alloy, the main components of which are Fe9.6-Si5.4-Al.

[0028] Example 1 Example 1 is a soft magnetic composite material, and the preparation method is as follows: 12.612 g of ammonium formate powder is added to 1 L of deionized water solution, and after dispersion, formic acid solution is added to adjust the pH to 4.4 to obtain an ammonium formate solution; the ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate are mixed in a mass ratio of 506:6:3, and ultrasonically dispersed for 15 minutes to obtain a mixed solution; the mixed solution is heated to 75°C in a water bath, kept at that temperature, and reacted with stirring for 1.5 hours; washed multiple times with ethanol and magnetically separated, then dried in an oven at 45°C for 23 days, and then heated at 380°C. The soft magnetic alloy powder coated with the Al2O3 layer was spread evenly on a quartz boat, which was then placed in a CVD rotary tubular furnace and heated to 400°C at 5°C / min under an argon protective atmosphere with a gas flow rate of 50 to 100 mL / min. Acetylene gas was then introduced at a flow rate of 25 mL / min to react for 1 hour to produce an amorphous carbon layer. After the reaction was completed, the acetylene gas was stopped and the powder was slowly cooled to 25°C and taken out to obtain the soft magnetic composite material of Example 1.

[0029] Measurement of electromagnetic wave absorption characteristics: The electromagnetic parameters of the sendust alloy of Comparative Example 1 and the soft magnetic composite material of Example 1 were measured. The measuring device was a vector analyzer, and the measurement frequency band was 0.5 to 18 GHz.

[0030] For the measurements, the Sendust alloy of Comparative Example 1 and the soft magnetic composite material of Example 1 were made into a coaxial ring, i.e., paraffin, the Sendust alloy of Comparative Example 1, and the soft magnetic composite material of Example 1 were thoroughly mixed in a mass ratio of 1:1 until homogeneous, and a coaxial ring with a thickness of approximately 2.5 mm, an inner diameter of approximately 3.0 mm, and an outer diameter of approximately 7.0 mm was produced.

[0031] Measurement results of electromagnetic wave absorption properties: Generally speaking, when RL<-10 dB, the material is considered to have an effective electromagnetic wave absorption bandwidth. In the frequency range of 0.5-18.0 GHz, the RL value of the sendust alloy of Comparative Example 1 is less than -10 dB in a bandwidth of less than 0.2 GHz, which indicates that the sendust alloy of Comparative Example 1 has a large limit in practical use. The soft magnetic composite material of Example 2 has an RLmin of -23.9 dB at 6.8 GHz, and the effective electromagnetic wave absorption bandwidth can reach 3.4 GHz.

[0032] The above-mentioned measurement results of the electromagnetic wave absorption properties show that the two-dimensional sheet-like multilayer structure of the soft magnetic composite material synthesized by first coating Al2O3 by the sol-gel method and then coating an amorphous carbon layer by the CCDV method has significantly improved minimum microwave loss value RLmin and effective bandwidth, etc., compared with the two-dimensional sheet-like single-layer structure of the Sendust alloy in Comparative Example 1, and the electromagnetic wave absorption properties of the electromagnetic wave absorbing powder have been greatly improved.

[0033] Comparative Example 2 and Example 2 provide an electromagnetic wave-absorbing film and a preparation method thereof.

[0034] Comparative Example 2 As shown in FIG. 1 , the electromagnetic-wave absorbing film of Comparative Example 2 includes a substrate 1 and an electromagnetic-wave absorbing layer 2 provided on the substrate 1. The electromagnetic-wave absorbing layer 2 uses the sendust alloy and polyurethane of Comparative Example 1. The preparation method of the electromagnetic-wave absorbing film includes the following steps: S1: A process of uniformly mixing sendust alloy and polyurethane to obtain a first mixture having a mass ratio of sendust alloy powder to polyurethane of 70:30. S2: Add the first mixture into a mixer, then add the solvent methyl isopropyl ketone, mix the solvent methyl isopropyl ketone and the first mixture in a mass ratio of 1:1, and stir thoroughly until homogeneous to obtain a second mixture; S3: A process in which the second mixture is applied onto a PET film (substrate 1), spread evenly over the surface of the PET film with a scraper, and then placed for 6 minutes on an acrylic plate having a plurality of cylindrical permanent magnets (height 2 mm, diameter 2 mm, spacing 6 mm) arranged in a lattice arrangement with their north poles facing upwards and with a residual magnetic flux density of 1 T, followed by heating, solidification and molding to form an electromagnetic wave absorbing layer 2, thereby obtaining an electromagnetic wave absorbing film of Comparative Example 2 in which the PET film is 100 μm thick and the electromagnetic wave absorbing layer 2 is 1 mm thick.

[0035] The electromagnetic-wave-absorbing film of Comparative Example 2 was cut to a size of 300×300 mm, and then its electromagnetic-wave absorption characteristics were measured. The measuring device was a vector analyzer, and the measurement frequency band was 1 to 40 GHz.

[0036] Measurement results of electromagnetic wave absorption properties: At 18GHz, RLmin was -20.1dB, and the effective electromagnetic wave absorption bandwidth could reach 7.9GHz.

[0037] Example 2 As shown in FIG. 1 , the electromagnetic-wave-absorbing film of Example 2 includes a substrate 1 and an electromagnetic-wave-absorbing layer 2 provided on the substrate 1. The electromagnetic-wave-absorbing layer 2 is made of the soft magnetic composite material of Example 1, i.e., polyurethane. The preparation method of the electromagnetic-wave-absorbing film includes the following steps: S1: uniformly mixing the soft magnetic composite material and polyurethane to obtain a first mixture in which the mass ratio of the soft magnetic composite material to the polyurethane is 70:30. S2: Add the first mixture into a mixer, then add the solvent methyl isopropyl ketone, mix the solvent methyl isopropyl ketone and the first mixture in a mass ratio of 1:1, and stir thoroughly until homogeneous to obtain a second mixture; S3: A process in which the second mixture is applied onto a PET film (substrate 1), and then uniformly spread over the surface of the PET film with a scraper. The mixture is then placed for 6 minutes on an acrylic plate having a plurality of cylindrical permanent magnets (height 2 mm, diameter 2 mm, spacing 6 mm) arranged in a lattice arrangement with their north poles facing upwards and each having a residual magnetic flux density of 1 T, followed by heating, solidification and molding to form an electromagnetic wave absorbing layer 2, thereby obtaining the electromagnetic wave absorbing film of Example 2 having a PET film thickness of 100 μm and an electromagnetic wave absorbing layer 2 thickness of 1 mm.

[0038] The electromagnetic-wave-absorbing film of Example 2 was cut into a size of 300×300 mm, and then its electromagnetic-wave absorption characteristics were measured. The measuring device was a vector analyzer, and the measurement frequency band was 1 to 40 GHz.

[0039] Measurement results of electromagnetic wave absorption properties: At 23 GHz, RLmin was -32.3 dB, and the effective electromagnetic wave absorption bandwidth could reach 15.1 GHz.

[0040] The present invention has many specific applications, and the above are only preferred embodiments of the present invention. It should be noted that the above examples are only used to interpret the present invention, and are not intended to limit the scope of protection of the present invention. Those skilled in the art can make some improvements without departing from the principle of the present invention, and these improvements should also be considered as the scope of protection of the present invention. [Explanation of symbols]

[0041] 1 Base material 2. Electromagnetic wave absorbing layer 21. Matrix 22 Electromagnetic wave absorbing unit

Claims

1. An electromagnetic wave absorbing film comprising a substrate (1) and an electromagnetic wave absorbing layer (2) provided on the substrate (1), the electromagnetic wave absorbing layer (2) comprising a matrix (21) and electromagnetic wave absorbing units (22), a plurality of the electromagnetic wave absorbing units (22) being arranged in a lattice pattern inside the matrix (21), the electromagnetic wave absorbing layer (2) comprising a soft magnetic composite material and a polymer elastomer, and a mass fraction of the soft magnetic composite material in the electromagnetic wave absorbing layer (2) being in the range of 10 to 80%, The method for preparing the electromagnetic wave-absorbing film includes the steps of: A step S1 of uniformly mixing the soft magnetic composite material and the polymer elastomer to obtain a first mixture; A step S2 of adding the first mixture into a stirrer, then adding a solvent, mixing the first mixture and the solvent in a mass ratio of 1 to 5:1 to 5, and stirring sufficiently until homogenous to obtain a second mixture; and a step S3 of applying the second mixture onto the substrate (1), spreading it evenly over the substrate (1) with a scraper, and then placing the mixture for 1 to 10 minutes on an acrylic plate provided with a plurality of cylindrical permanent magnets arranged in a lattice arrangement with their north poles facing upwards, and then heating, solidifying and shaping the mixture to obtain the electromagnetic wave absorbing film, The method for preparing the soft magnetic composite material comprises the steps of: Ammonium formate solution, soft magnetic alloy powder, and aluminum sulfate are mixed and ultrasonically dispersed for 10 to 3 minutes to obtain a mixed solution, the mixed solution is heated in a water bath at 75 to 85°C, and is reacted while being kept at that temperature for 1 to 2 hours while being stirred. After washing with ethanol several times and magnetic separation, it is dried in an oven at 40 to 50°C for 1 to 3 days, and then annealed at 350 to 450°C for 2 hours to obtain Al. 2 O 3 A step S1 of obtaining a soft magnetic alloy powder coated with a layer; A 2 O 3 The soft magnetic alloy powder coated with the layer is spread evenly on a quartz boat, then placed in a CVD rotary tubular furnace, heated to 400° C. at 3-6° C. / min under an argon protective atmosphere with a gas flow rate of 50-100 mL / min, and then reacted for 0.5-1 hour by introducing acetylene gas at a flow rate of 20-30 mL / min. After the reaction is completed, the acetylene gas is stopped, the powder is slowly cooled to 25° C., and the powder is taken out to obtain the soft magnetic composite material. Electromagnetic wave absorbing film.

2. 2. The electromagnetic-wave-absorbing film according to claim 1, wherein the soft magnetic composite material is a powder, the powder has a thickness of 0.5 to 1.5 μm, and the powder has a particle size D50 in the range of 30 to 100 μm.

3. The soft magnetic composite material is made of a soft magnetic alloy from the inside to the outside. 2 O 3 3. The electromagnetic-wave-absorbing film according to claim 2, which has a two-dimensional sheet-like multilayer structure including a carbon nanotube layer, an amorphous carbon layer, and an amorphous carbon layer.

4. 4. The electromagnetic-wave-absorbing film according to claim 3, wherein the soft magnetic alloy is at least one selected from the group consisting of an iron-silicon-aluminum soft magnetic alloy, an iron-silicon soft magnetic alloy, an iron-nickel soft magnetic alloy, an iron-nickel-molybdenum soft magnetic alloy, an iron-aluminum soft magnetic alloy, an iron-silicon-aluminum-nickel soft magnetic alloy, an iron-chromium soft magnetic alloy, and an iron-cobalt soft magnetic alloy.

5. 2. The electromagnetic-wave absorbing film according to claim 1, characterized in that the substrate (1) is at least one of a PET film, a PI film, a PP film, a PEI film, a polyether ether ketone, a phenolic resin, a PE film, a PC film, a PS film, and a PVC film, the substrate (1) having a thickness of 10 to 300 μm, and the electromagnetic-wave absorbing layer (2) having a thickness of 0.1 to 2 mm.

6. The electromagnetic-wave-absorbing film according to claim 1 , wherein the polymer elastomer is at least one of polyurethane, acrylic acid, organosilicon, and epoxy resin.

Citation Information

Patent Citations

  • Novel nanocrystalline composite material and preparation process thereof

    CN106298139A

  • Magnetic wave-absorbing metamaterial and preparation method thereof

    CN114498067A

  • Electromagnetic wave absorbing sheet and manufacturing method therefor

    JP2008198873A